PENGARUH MODEL PEMBELAJARAN INKUIRI DENGAN BANTUAN APLIKASI QREATIF EDUKATIF TERHADAP PEMAHAMAN KONSEP IPA SISWA SEKOLAH DASAR - Gina Selvia Rahayu; Fitri Nureani; Tiara Yogiarni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Conceptual understanding is an important part of science learning, as it allows students to relate the material to real-life experiences and think scientifically. However, the low conceptual understanding remains a major issue in elementary schools, caused by science education being dominated by conventional teaching methods. This study aims to determine the effect of the guided inquiry learning model assisted by the Qreatif Edukatif application on the understanding of science concepts among elementary school students. This study adopts a quantitative approach with a quasi-experimental method. The research design used is a quasi-experimental Nonequivalent Control Group Design, with subjects in the experimental class consisting of 28 samples and the control class consisting of 31 students. Data were collected through multiple-choice test instruments adjusted to the indicators of science concept understanding, namely giving examples, explaining, classifying, concluding, and interpreting. Then the data were analyzed using descriptive statistics, normality test, homogeneity test, regression, and t-test. The results show a significant increase in the posttest scores of the experimental class with a mean score of 79.03 compared to the control class mean score of 63.22. Regression analysis indicates that the inquiry model contributed 45.2% to the improvement in conceptual understanding. The N-Gain score of the experimental class was 66% (moderate and quite effective category), while the control class was 35% (low category). It can be concluded that the guided inquiry model with the help of the Qreatif Edukatif application effectively influences and enhances students' understanding of science concepts. Further research is recommended to expand the focus of the study to include a wider range of concept comprehension indicators.